2023
DOI: 10.3389/fsufs.2022.1078997
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and its footprints: Using environmental indicators to assess the nexus between sustainability and food

Abstract: Current food systems are associated with the unsustainable use of natural resources; therefore, rethinking current models is urgent and is part of a global agenda to reach sustainable development. Sustainable diets encompass health, society, economy, culture as well as the environment, in addition to considering all the stages that make up the food production chain. This study aimed to perform a review on the importance of using environmental footprints (EnF) as a way of assessing the environmental impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…Although the literature has been growing recently on that topic (19), a lower number of studies have focused on WU in food systems compared to those on GHGs and the footprint indicators used were not consistent (blue, green, or blue and green). Thus, according to a recent review the carbon footprint has been studied twice as much than the water footprint (whatever the indicator used) (30) but the two indicators are rarely studied concomitantly. Furthermore, in diet modeling studies about environmental footprint reductions, environmental indicators were generally included as constraints and not as objectives/targets to be minimized (11), which makes not possible to assess the extent of their maximal improvements and their potential conflicts or alignments.…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature has been growing recently on that topic (19), a lower number of studies have focused on WU in food systems compared to those on GHGs and the footprint indicators used were not consistent (blue, green, or blue and green). Thus, according to a recent review the carbon footprint has been studied twice as much than the water footprint (whatever the indicator used) (30) but the two indicators are rarely studied concomitantly. Furthermore, in diet modeling studies about environmental footprint reductions, environmental indicators were generally included as constraints and not as objectives/targets to be minimized (11), which makes not possible to assess the extent of their maximal improvements and their potential conflicts or alignments.…”
Section: Discussionmentioning
confidence: 99%
“…In a broad context, both the vegetarian diet and the non-vegetarian diet contribute to the GHG burden, however, the burden of the latter is more than 2.5 times greater (4.2 vs. 1.6 kgCO2eq/day; Rabès et al, 2020). In other words, the overall environmental impact of non-vegetarian diets is higher than vegetarian diets by about 60% (Rabès et al, 2020;Hatjiathanassiadou et al, 2023). In that sense, available evidence indicated that a change in global diet patterns could result in up to a 50% reduction in GHG emissions (Hallström et al, 2015).…”
Section: Introductionmentioning
confidence: 99%